RETRACTED: lncRNA-XLOC_012370 Promotes the Development of Pancreatic Cancer and Inactivates the NF-κB Pathway Through miR-140-5p - Han-Xiao Nie; Ling Zhang; Tao He; Li Wang; Bai-Shun Wan; Xiao-Qian Wang; Feng Han (Frontiers in Oncology, 2021)
Pancreatic cancer is a high incidence, high degree of malignancy, and high mortality in the digestive system tumor. The incidence of pancreatic cancer in China has increased nearly six folds in the past 20 years, ranking fifth in the mortality rate of malignant tumors, so it is particularly important to actively explore clinical indicators with better diagnostic significance for pancreatic cancer. LncRNA performs an essential regulatory function in the occurrence, development, and metastasis of many kinds of tumors, playing both a carcinogenic role and a tumor suppressor gene. Here, we demonstrated the function and mechanism of LncRNA-XLOC_012370 in the development of pancreatic cancer. In our research, the abnormal upregulation of XLOC_012370 was observed in pancreatic cancer patients’ tumor tissues. XLOC_012370 was related to tumor stage, lymph node metastasis, and overall survival. Silencing of XLOC_012370 prevented the proliferation, migration, and invasion via the NF-κB signal pathway. Further, miR-140-5p was identified as the target and downstream of XLOC_012370 and involved in pancreatic cancer progression. In vivo, knockdown of XLOC_012370 inhibited tumor growth via the NF-κB signal pathway. In conclusion, lncRNA-XLOC_012370 is closely related to some malignant clinicopathological features and prognosis of pancreatic cancer. Thus the miR-140-5p/NF-κB signal pathway might represent a promising treatment strategy to combat pancreatic cancer.